The Brawner Rule—New Lyrics for an Old Tune - Richard C. Allen (Washington University Law Quarterly, 1973)
Following a discussion of the recommendations made by the amici concerning the insanity defense and issues surrounding it, the author will consider a proposal rejected by the Brawner court: abolition of the insanity defense.
Keywords: Brawner v. United States; 417 F.2d 969 (1972)